Keseimbangan Perlindungan Hukum antara Anak Pelaku dan Anak Korban dalam Tindak Pidana Pencabulan - SARI TIRTA RAHAYU (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The crime of child molestation involving both perpetrators and victims raises issues regarding the balance of legal protection in the juvenile criminal justice system. This study aims to analyze the legal protection provisions for child perpetrators and victims in Indonesian positive law. The method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that Law Number 11 of 2012 concerning the Juvenile Criminal Justice System places greater emphasis on protecting child perpetrators through diversion and guidance, while the provision of rehabilitation for child victims has not been comprehensively regulated. Therefore, it is necessary to strengthen the provisions for rehabilitation, psychological assistance and restitution for child victims, as well as the development of integrated implementation guidelines by law enforcement officials.